UVIT view of Centaurus A: a detailed study on positive AGN feedback. Issue 2 (2nd September 2022) - Joseph, Prajwel; Sreekumar, P; Stalin, C S; Paul, K T; Mondal, Chayan; George, Koshy; Mathew, Blesson
ABSTRACT: Supermassive black holes at the centre of active galactic nuclei (AGNs) produce relativistic jets that can affect the star formation characteristics of the AGN hosts. Observations in the ultraviolet (UV) band can provide an excellent view of the effect of AGN jets on star formation. Here, we present a census of star formation properties in the Northern Star-forming Region (NSR) that spans about 20 kpc of the large radio source Centaurus A hosted by the giant elliptical galaxy NGC 5128. In this region, we identified 352 UV sources associated with Cen A using new observations at an angular resolution of <1.5 arcsec observed with the Ultra-Violet Imaging Telescope (UVIT) onboard AstroSat. These observations were carried out in one far-ultraviolet (FUV; λmean = 1481 Å) and three near-ultraviolet (NUV; with λmean of 2196, 2447, and 2792 Å, respectively) bands. The star-forming sources identified in UV tend to lie in the direction of the jet of Cen A, thereby suggesting jet triggering of star formation. Separating the NSR into Outer and Inner regions, we found the stars in the Inner region to have a relatively younger age than the Outer region, suggesting that the two regions may have different star formation histories. We also provide the UVIT source catalogue in the NSR.